2001
DOI: 10.2486/indhealth.39.281
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Assess Low Frequency Noise in the Working Environment.

Abstract: To assess high-level low frequency noise in the working environment, adverse extra-aural effects caused by the noise should be taken into account. The human body vibration induced by low frequency noise, 'noise-induced vibration', was measured on the body surface and the equalacceleration level contours of the vibration were tentatively estimated. With these contours, we can predict the magnitude of noise-induced vibration at every measuring position on the body surface. This is helpful in relating the total d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For practical use, it is preferable that a frequency-weighting characteristic corresponding to an evaluation index is available. In a previous study using lowfrequency pure tones as noise stimuli, the equal-acceleration level contour was considered to be a contour connecting the sound pressure levels at which equal VALs of noise-induced vibrations were induced, and roughly estimated the contour in the 25-to 50-Hz range [22]. Using the notation of the present study, the equalacceleration level contours estimated at the chest can be expressed approximately as SPL = -50 x log 10 (f) + VAL + 90, where f is the frequency [Hz] and SPL is the non-weighted sound pressure level [dB(SPL)] of a low-frequency noise stimulus.…”
Section: Estimation Of Frequency-weighting Characteristics Correspondmentioning
confidence: 99%
See 1 more Smart Citation
“…For practical use, it is preferable that a frequency-weighting characteristic corresponding to an evaluation index is available. In a previous study using lowfrequency pure tones as noise stimuli, the equal-acceleration level contour was considered to be a contour connecting the sound pressure levels at which equal VALs of noise-induced vibrations were induced, and roughly estimated the contour in the 25-to 50-Hz range [22]. Using the notation of the present study, the equalacceleration level contours estimated at the chest can be expressed approximately as SPL = -50 x log 10 (f) + VAL + 90, where f is the frequency [Hz] and SPL is the non-weighted sound pressure level [dB(SPL)] of a low-frequency noise stimulus.…”
Section: Estimation Of Frequency-weighting Characteristics Correspondmentioning
confidence: 99%
“…Frequency-weighting characteristics corresponding to the HLLF indices Using the equal-acceleration level contours estimated at the chest[22], the HLLF1 index could be rewritten asHLLF1 = 0.045 x [SPL + C A (f)] + 0.062 x [SPL + 50 x log 10 (f) -90 + C k (f)] -5.0 = 0.107 x [SPL + 0.42 x C A (f) + 0.58 x C k (f) + 29 x log 10 (f)]-10.6 where C A (f) and C k (f) represent the correction functions for the A-and W kweighting characteristics as C A (f) and C k (f), respectively. By regarding the correction terms for the SPL in brackets as a frequency-weighting function, we temporarily defined the tentative HLLF1-weighting characteristic as C HLLF1 (f) = 0.42 x C A (f) + 0.58 x C k (f) + 29 x log 10 (f).…”
mentioning
confidence: 99%
“…Infrasound can also be produced by devices used in daily life such as woofers, vehicle structures, and fans. Research has indicated that prolonged exposure to infrasound forms a serious health risk [65]. On the other side of the spectrum, ultrasound encompasses all sound with a frequency larger than the upper limit of the human hearing (20 KHz).…”
Section: Introductionmentioning
confidence: 99%